Effect of Hygrothermal ageing on mechanical properties, swelling behavior and morphology of wood powder filled Low-density Polyethylene (LDPE) - Norazraini Afiqa Mohd Jamari (Universiti Malaysia Perlis, 2008)
Effect of hygrothermal ageing on mechanical properties, swelling behavior and morphology of wood powder filled LDPE with different filler loading and addition of coupling agent was investigated and compared with each other. Maleic acid and COCA Coconut Oil Coupling Agent) were used as the coupling agent to enhance adhesion between filler and matrix. The result indicated that tensile strength and Young’s modulus are lower for the hygrothermal ageing sample compare to the before ageing although it is increasing with further filler loading but have the opposite pattern for elongation at break. Composite with coupling agent of maleic acid is giving the higher tensile strength and Young’s modulus but lower elongation at break than the sample with coupling agent of COCA. Swelling behavior indicates that the water absorption ability is increase rapidly for the first two weeks but gradually increase after that until it reach its moisture equilibrium. SEM morphology study indicate that LDPE/wood powder with maleic acid and COCA causing the fracture surface of the sample to be softer thus ductile after hygrothermal ageing than before ageing.